1996
DOI: 10.1006/dbio.1996.0122
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Lesions and Skeletal Myopathy in Mice Lacking Desmin

Abstract: In order to further our understanding of the biological role of desmin, the muscle-specific intermediate filament protein, a null mutation in the desmin gene was introduced into the germ line of mice. Despite the complete lack of desmin, these mice developed and reproduced. Since we show that skeletal, cardiac, and smooth muscles form in the Des-/- mice, it is reasonable to propose that desmin is not essential for myogenic commitment or for myoblast fusion or differentiation in vivo. However, morphological abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
238
3
14

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(264 citation statements)
references
References 0 publications
9
238
3
14
Order By: Relevance
“…Ablation of desmin expression in mice by gene targeting 21 has demonstrated that desmin expression is crucial for maintaining the architectural and functional integrity of striated muscle. Mice lacking desmin develop numerous muscle architectural and ultrastructural defects, especially in extensively used muscles such as the heart, soleus and diaphragm.…”
Section: Intermediate Filaments Of the Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Ablation of desmin expression in mice by gene targeting 21 has demonstrated that desmin expression is crucial for maintaining the architectural and functional integrity of striated muscle. Mice lacking desmin develop numerous muscle architectural and ultrastructural defects, especially in extensively used muscles such as the heart, soleus and diaphragm.…”
Section: Intermediate Filaments Of the Musclementioning
confidence: 99%
“…21,23,81 Some cell architecture defects such as misaligned muscle fibers, abnormal sarcomeres, swollen mitochondria and unusual distribution of myosins are seen in earlier stages of development. 86 After birth, irregularities in the myofibrillar organization are predominantly observed in the extensively used skeletal muscles such as the tongue, diaphragm and the soleus muscle.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those mice developed a progressive and generalized myopathy that mainly affected the myocardium. The striated muscles that were examined all showed irregular mitochondrial shape and distribution, including aggregation of sarcolemmal mitochondria, which correlated with weakened muscles and increased fatigue 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…The ability of desmin and syncoilin to inter-act provides evidence for an important association between IF proteins at the Z-lines in muscle and the extracellular matrix via the DAPC. Mutations in the desmin gene cause myopathy together with cardiomyopathy (13). Syncoilin, like desmin, is up-regulated in some muscular dystrophies, making it a candidate gene for muscular dystrophy as well as cardiomyopathy.…”
mentioning
confidence: 99%